STRENGTHENING THE CAPACITY OF MOSQUE YOUTH COMMUNITIES IN ACEH BESAR REGENCY TO COUNTER BRAINWASHING AND DESTRUCTIVE CYBERBULLYING THROUGH SOCIAL MEDIA LITERACY - Jarnawi, Jarnawi; Fairus, Fairus; Nurarafah, Nurarafah; Rahmatillah, Syauqas; Intan Khairina, Mashitah (Al-Mubin, 2025)
Mosque youth in Aceh Besar Regency are a vulnerable group exposed to radicalism on social media, often framed through religious issues. A community engagement program in the form of mentoring for this group can serve as an effort to raise awareness, build understanding, and develop media literacy skills. This initiative targets individuals from Generations X, Y, and Z who have strong religious habituation within the mosque environment, ensuring they are not trapped by hoaxes and radical narratives disguised as religious tendencies. The goal is to prevent their enthusiasm for social media from becoming a medium for brainwashing, cyberbullying, and mobilization towards radical thinking and actions, which could ultimately lead to legal consequences